1971
DOI: 10.1097/00004397-197101140-00033
|View full text |Cite
|
Sign up to set email alerts
|

The Accommodation Requirement in Myopia and Hyperopia Contact Lenses versus Spectacles

Abstract: In a later investigation of accommodation and convergence Alpern5 stated that, from his own experience, the increase of accommodation of one eye was invariably accompanied by an inward ro¬ tation of the other (occluded) eye, and that this movement seems to be more closely related to the actual change in accommodation than to a change

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We should add that the subjects were students of optometry, and therefore clearly understood the instructions on methodology. Theoretical differences in accommodation and vergence demands when wearing single vision SCL compared to spectacle lenses have been established with the support of clinical results [13,14,16,35]. For the sake of convention, accommodation is usually considered to take place at the spectacle plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should add that the subjects were students of optometry, and therefore clearly understood the instructions on methodology. Theoretical differences in accommodation and vergence demands when wearing single vision SCL compared to spectacle lenses have been established with the support of clinical results [13,14,16,35]. For the sake of convention, accommodation is usually considered to take place at the spectacle plane.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters, such as negative relative accommodation (NRA), positive relative accommodation (PRA), binocular accommodative facility, stimulus AC:A ratio, and stereoacuity, are used to evaluate the interaction between the vergence and accommodative systems. Even though it is well-known that accommodation and vergence demands depend on the type of optical correction, only a few studies [13,[35][36][37] examine the clinical differences between these parameters in myopes when contact lenses are used as opposed to spectacles. In addition, all of these studies were carried out many years ago, when the material, design, and technical characteristics of SCL were different from those currently available.…”
Section: Introductionmentioning
confidence: 99%
“…The significant findings were myopes require increased accommodation and increased convergence when wearing CLs compared to spectacles, while the opposite occurs for hyperopes. 351 These findings were confirmed clinically for myopes by Hermann and Johnson, 352 while Robertson et al performed a clinical trial and confirmed increased accommodation was required by myopes wearing CLs compared to specacles. 353 In addition to differences between CLs and spectacles for accommodation and convergence, CLs also reduce aniseikonia effects compared to spectacles, which makes them a more ideal correction in cases of anisometropia.…”
Section: The Effect Of Contact Lenses On Binocular Visionmentioning
confidence: 74%
“…Myopia as a condition affects several binocular vision (BV) measurements, [338][339][340][341][342][343][344][345][346][347] but does not appear to increase the risk of a BV-disorder. 279,350 However, myopic CL wear Chapter 9: Summary and conclusions increases both the accommodation [351][352][353] and convergence 351,352 required compared to wearing of spectacles, while negative spherical aberration, present in many commercially available single vision (SV) CLs, 360,361,365 further increases required accommodation. 366,367 The increased effects on the accommodative and vergence systems with CLs should not induce symptoms beyond what is experienced in spectacles for young myopes with a normal BV system due to the increased convergence stimulated by increased accommodation assisting with the required increased convergence.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical differences in vergence demands and oculomotor response have been established when changing from spectacle lens to single vision contact lens wear [62][63][64]. Myopes fixating at a near target through spectacle lenses experience an induced base in prismatic effect, resulting in a decreased stimulus for convergence [63].…”
Section: Discussionmentioning
confidence: 99%